Contagion Risk in the International Banking System and Implications for London As a Global Financial Center - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2007)
In this paper, we use the extreme value theory (EVT) framework to analyze contagion risk across the international banking system. We test for the likelihood that an extreme shock affecting a major, systemic U.K. bank would also affect another large local or foreign counterpart, and vice-versa. Our results reveal several key trends among major global banks: contagion risk among banks exhibits "home bias"; individual banks are affected differently by idiosyncratic shocks to their major counterparts; and banks are affected differently by common shocks to the real economy or financial markets. In general, bank soundness appears more susceptible to common (macro and market) shocks when the global environment is turbulent; this may have important implications for London as a major financial services and capital markets hub.